2018
DOI: 10.2355/isijinternational.isijint-2018-336
|View full text |Cite
|
Sign up to set email alerts
|

<i>In situ</i> Neutron Diffraction Study on Ferrite and Pearlite Transformations for a 1.5Mn-1.5Si-0.2C Steel

Abstract: The phase transformation behavior from austenite upon cooling in a 1.5Mn-1.5Si-0.2C steel was in situ monitored using dilatometry, X-ray and neutron diffractions. The starting temperature of ferrite transformation was in good agreement between dilatometry and neutron diffraction, whereas much higher in X-ray diffraction. Such a discrepancy in transformation temperature is attributed to the change in chemical composition near the surface of a specimen heated to elevated temperatures in a helium gas atmosphere f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The plane peaks (110) and (211) are reflections of the α-iron (ferrite) phase. These α-iron phase plane peaks are in good agreement with the results of other studies [26][27][28]. The peak magnification of 110 plane diffraction patterns in the inset of Figure 3 (2θ = 50-53°) shows an asymmetric peak shape.…”
Section: Xrdsupporting
confidence: 91%
“…The plane peaks (110) and (211) are reflections of the α-iron (ferrite) phase. These α-iron phase plane peaks are in good agreement with the results of other studies [26][27][28]. The peak magnification of 110 plane diffraction patterns in the inset of Figure 3 (2θ = 50-53°) shows an asymmetric peak shape.…”
Section: Xrdsupporting
confidence: 91%
“…Although sample SS revealed a higher YS of 539 MPa than that of sample AB without a plateau, it exhibited degraded performance, showing a TE of 1113 MPa at a UE of 5.78%, and fracture at 15.7%. This indicated that sample AB with a large amount of retained austenite had an advantage in The interstitial atom concentration and residual stress are key factors in determining the lattice parameters [21][22][23][24]. Since interstitial atoms are less soluble in BCT martensite, the decrease in the BCT lattice parameter was caused by the diffusion of interstitial atoms with heterogeneous distributions into austenite with a higher solubility [2,17,25], as well as the attenuation of martensite defects (a tempering effect) [26], both of which occurred during the aging process.…”
Section: Evolution Of Tensile Behaviormentioning
confidence: 98%
“…The phase fraction of austenite grew to 60.8% at the aging temperature of 400 • C, and this increasing tendency persisted up to the aging temperature of 490 • C (62.6%). The sample aged at 520 • C showed a relatively low fraction of retainued austenite (57%) and at increasing temperatures of aging treatment, the fraction of retained austenite continued to decline, reaching 15.9% at the aging temperature of 700 • C. The interstitial atom concentration and residual stress are key factors in determining the lattice parameters [21][22][23][24]. Since interstitial atoms are less soluble in BCT martensite, the decrease in the BCT lattice parameter was caused by the diffusion of interstitial atoms with heterogeneous distributions into austenite with a higher solubility [2,17,25], as well as the attenuation of martensite defects (a tempering effect) [26], both of which occurred during the aging process.…”
Section: Microstructural Evolutionmentioning
confidence: 99%